Fetal head circumference versus fetal weight at term as a predictor of labour outcome - Shettian, Nishita; Pitty, Nikita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Several models have been proposed to predict the need for an LSCS. With reference to this, the impact of the size of the fetal head traversing the birth canal is an important determinant of delivery outcomes. We examined the association between the head circumference and mode of delivery and perinatal outcomes, when compared to birth weight predicted by scan. Methods: This was a retrospective study, on 800 electronic delivery records between December 2019 and May 2021. Sociodemographic data, obstetrical parameter, term scan findings of head circumference and estimated fetal weight, and labour and perinatal outcomes were collected and analysed. Results: HC >95th centile was found to be comparatively more predictive and statistically significant compared to EFW >95th centile in the prediction of LSCS, with the most common indication being cephalopelvic disproportion. Prolonged second stage of labour was statistically significant in both cohort A and B, undergoing vaginal delivery. It was also noted that a significant number of newborns in cohort A required NICU admissions, while NICU admissions after emergency LSCS was significantly higher in the cohort B (p=0.0032) though the overall 5 and 10 minute APGAR scores and duration of stay were comparable in the groups classified on basis of EFW and HC. Conclusions: The above statistics observed on an Indian population may aid obstetricians in the planning of the mode of delivery, improve pre-labor counselling and efficient management of mothers of large babies.